Integrasi Perspektif Bisnis Islam: Definisi, Pentingnya, Etika, dan Landasan dalam Al-Quran sebagai Panduan Praktik Bisnis Berkelanjutan - Chairun Nisa Panjaitan; Naylatusalwa Makarim Tambunan; Sarah Febrian (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to define the concept of Islamic business, analyze the importance of business ethics in Islam, and explain the basis in the Al-Qur'an as a guide to sustainable business practices. This research uses a qualitative method with a library research approach, where researchers collect and analyze data from various relevant literature, including books, scientific articles, journals and other written sources. This research shows that the Islamic business concept does not only focus on achieving financial profits, but is also based on sharia principles which emphasize moral and ethical values, such as justice, transparency and social responsibility. Through studying the verses of the Qur'an and applying ethical principles in business practices, it was found that honesty in transactions and commitment to the welfare of society are very important aspects.